International Capital Flows and the Allocation of Credit Across Firms - Daniel Marcel te Kaat (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Substantial research yields opposing conclusions regarding the effects of international capital flows on economic growth. However, microeconomic channels that help to explain these inconsistencies are to date underexplored. This paper overcomes intricate identification issues by using a comprehensive dataset that covers about 20,000 firm-year observations to study the effects of the exogenous fluctuations in European capital flows on bank lending and the real behavior of firms from 1995-2014. We find that higher capital inflows are associated with more loans to less profitable firms, thereby, impeding the creative economic destruction. Consequently, there is evidence for time-varying implications of foreign capital for economic growth.
Keywords: F32; F43; G21; 330